Development of a Reagent Kit for the Quantitative Determination of Hepatitis B Virus (HBV) DNA in Clinical Material by PCR with Hybridization-Fluorescence Detection - O. N. Zhigaleva; S. G. Mardanly; T. Yu. Gashenko; I. I. Ermolaev (Эпидемиология и вакцинопрофилактика)
Relevance. Hepatitis B virus (HBV) is one of the most common viral infections affecting people worldwide and can lead to chronic hepatitis, cirrhosis and hepatocellular carcinoma. Currently 3% of the world's population are infected with hepatitis B virus and are at risk of developing life-threatening liver disease. Immunological and molecular biological methods of detection of HBV are currently used in laboratory diagnostics. The polymerase chain reaction (PCR) is currently the most sensitive method for the detection and quantification of HBV. HBV DNA quantification is widely used to monitor the antiviral treatment of HBV infection.Aim. To develop a real-time PCR kit for the quantification of HBV DNA.Materials and methods. A total of 200 plasma and serum samples positive and negative for HBV were used in the development. The performance of the developed kit was compared with the use of other commercially registered HBV diagnostic kits in Russia. Additionally, the nucleotide sequences of all existing virus genotypes analysed for the selection of primers using GeneBank system.Results and discussion. Comparison analysis of the results of quantitative determination by real-time PCR in 200 clinical serum and blood plasma samples showed that the diagnostic sensitivity of the developed kit was 100% and specificity 100%. The primers developed specific to the POL gene region. The kit is capable of detecting all types of virus genotypes.Conclusions. The developed reagent kit allows detection of hepatitis B virus and determination of its quantity within 70 minutes. In addition to a large number of genotypes and subgenotypes, the virus is characterized by mutational changes in the genome, which complicates its diagnosis and, as a consequence, the ongoing therapy with drugs. Conservative regions for primer and probe selection taken into account in the development, and the sequencing results obtained are applicable to all HBV genotypes. The reagent kit is designed to monitor HBV infected patients and will allow the analysis of different HBV viral loads.